2010
DOI: 10.1159/000321828
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Total Tear and Serum IgE in Allergic Conjunctivitis

Abstract: Background: Recently, a new commercial test for total tear IgE based on immunochromatography (Allerwatch®) was developed. We examined the relationship between total tear and serum IgE levels with the Allerwatch test. Methods: A nonrandomized cross-sectional study was conducted in 40 patients with allergic conjunctivitis, 35 age- and sex-matched healthy control subjects, and 6 patients with epidemic keratoconjunctivitis (EKC). The total tear IgE score was determined with the Allerwatch test (0, 1 and 2), and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 23 publications
2
18
1
Order By: Relevance
“…[3][4][5] Recent development of a rapid immunoassay for measuring total IgE has now made it possible to measure total IgE tear levels. [6][7][8][9][10][11] Two allergic conjunctivitis peaks are observed in Japan, with one each occurring in the spring and autumn. 1,2 We previously reported finding a strong correlation between the total tear IgE score and specific serum IgE antibodies for cedar pollen in patients with allergic conjunctivitis during the spring.…”
mentioning
confidence: 99%
“…[3][4][5] Recent development of a rapid immunoassay for measuring total IgE has now made it possible to measure total IgE tear levels. [6][7][8][9][10][11] Two allergic conjunctivitis peaks are observed in Japan, with one each occurring in the spring and autumn. 1,2 We previously reported finding a strong correlation between the total tear IgE score and specific serum IgE antibodies for cedar pollen in patients with allergic conjunctivitis during the spring.…”
mentioning
confidence: 99%
“…19,20 High levels of IgE have been detected in the patients with vernal Keratoconjunctivitis (VKC), while mild levels of IgE were found in the tears of patients with perennial AC. 20,21 Mimura et al 23 found a positive correlation between tear and serum IgE in the patients with AC. Increased level of serum IgE was also determined in other allergic disorders such as bronchial asthma and atopic dermatitis.…”
Section: Discussionmentioning
confidence: 93%
“…Increased level of serum IgE was also determined in other allergic disorders such as bronchial asthma and atopic dermatitis. [22][23][24] IgE presents binding sites for This cross-linking of the IgE surface to antigen on mast cells promotes the production of mediators. 25 We found that the level of total IgE and OVA-specific IgE was reduced significantly in the mice exposed to OVA on ocular administration of TQ.…”
Section: Discussionmentioning
confidence: 99%
“…Determination of the total IgE level in tear fluid (total tear IgE) was performed with the Allerwatch Ò test according to the manufacturer's instructions [16][17][18][19][20][21][22][23][24][25]. In brief, the filter strip was placed at the lower fornix of the right eye, and was removed when tear fluid reached the control line.…”
Section: Determination Of Total Ige In Tear Fluidmentioning
confidence: 99%